The isolation and properties of cardiac ribosomes and polysomes - Earl, D. C. N. (1965)
1. A method is described by which good yields of ribosomes and polysomes free of contamination by submitochondrial fragments can be prepared from rat cardiac muscle. These preparations are capable of incorporation of amino acids into protein in vitro. 2. The ribosome preparation consists of 32% of monomeric ribosomes and 68% of ribosomal aggregates or polysomes. The polysome preparation has a decreased monomeric content. Dimers, trimers, tetramers, pentamers and larger components can be differentiated. 3. The polysome aggregate structure is degraded to monomeric ribosomes on incubation with small amounts of ribonuclease or by preparation in the absence of Mg(2+) ions. The degradation in the absence of Mg(2+) ions was not reversible and drastically decreased the incorporation of amino acids in vitro. 4. The cardiac ribosomes contained two major RNA species sedimenting at 19s and 28s in a 1:2·4 ratio. 5. The RNA/protein ratio of cardiac ribosomes and polysomes was consistently lower than that of similar preparations from liver. The concentrations of Na(+) and K(+) ions present during preparation had a great effect on the RNA/protein ratio. 6. Optimum conditions for the incorporation of amino acids into protein in vitro are reported. Cardiac ribosomes have a lower rate of incorporation of amino acids in vitro than liver ribosomes. 7. Heart cell sap is less active than liver cell sap: evidence is presented that a factor, present in liver cell sap and concerned with stimulating the synthesis of the peptide chain, is lacking in heart cell sap. 8. Pulse-labelling of perfused hearts followed by examination of the subcellular structures showed that the ribosomal fraction was the most active in the incorporation of amino acids in vitro.